Ezekiel's "living beings" in Pseudo-Ezekiel 4Q385, Frg. 6: a comparison with key angelological verses in Ezekiel 1 and 10 - Evans, Annette (Old Testament essays, 2017)
Earlier research has demonstrated that certain ambiguous angelo-logical phrases which hint at divinatory associations present in MT Ezek 1 and 10 (the so-called "Merkebah Chapters") have been suppressed in the LXX version. As a translation, the LXX reflects the religious needs and exegetical perceptions of the Alexandrian Jews in the third and second centuries BCE. This article compares these key angelological verses in Ezek 1 and 10 with linguistically or semantically similar words or phrases in 4Q385 Pseudo-Ezekiel. The result of the comparison indicates that these telltale verses are contradicted in Pseudo-Ezekiel 4Q385 Frg. 6. The Dead Sea Scrolls share aspects and problems of beliefs in angels with the Judaism of their period, but the texts found at Qumran increase the difficulty of defining Jewish angelology, partly because of lack of knowledge concerning their provenance, and partly because the different works show quite disparate beliefs and motives concerning angels. The conclusion of this article is that Pseudo-Ezekiel was written by a conservative author who on the one hand did not want to reveal the divinatory aspects of the angelological content, but on the other hand was innovative.